1995
DOI: 10.1002/prot.340230410
|View full text |Cite
|
Sign up to set email alerts
|

Hinge‐bending motion in citrate synthase arising from normal mode calculations

Abstract: A normal mode analysis of the closed form of dimeric citrate synthase has been performed. The largest-amplitude collective motion predicted by this method compares well with the crystallographically observed hinge-bending motion. Such a result supports those obtained previously in the case of hinge-bending motions of smaller systems, such as lysozyme or hexokinase. Taken together, all these results suggest that low-frequency normal modes may become useful for determining a first approximation of the conformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
196
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 192 publications
(204 citation statements)
references
References 24 publications
(1 reference statement)
8
196
0
Order By: Relevance
“…(Aj) and (⌬R) represent the corresponding root mean square values. The overlap O j describes the similarity between the direction of observed conformational change and the jth normal mode of the protein (29). It is defined:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Aj) and (⌬R) represent the corresponding root mean square values. The overlap O j describes the similarity between the direction of observed conformational change and the jth normal mode of the protein (29). It is defined:…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the trajectory of protein motion will rarely be in a straight line, and therefore an otherwise correctly predicted initial direction of motion might deviate noticeably from the observed conformational change (22). Despite these limitations, many studies have found agreement between features of the motion predicted by NMA and the observed or simulated conformational change of one or a small number of proteins (23)(24)(25)(26)(27)(28)(29)(30). A number of large-scale studies have assessed the success of normal modes at describing protein motion as defined by the database of macromolecular movements (31).…”
mentioning
confidence: 99%
“…This is a valid assumption especially for supermolecular complexes, in which the functionally important conformational changes, such as domain movements (3), are mediated by collective global deformational motions of the structure. As shown in numerous studies of the standard normal mode analysis (NMA) (4)(5)(6)(7)(8)(9)(10)(11)(12), the pathways of the functionally important conformational changes can be matched by the intrinsic low-energy deformational modes. Moreover, these collective global motions are not sensitive to the local connectivity of the molecular structure, instead, they are primarily influenced by the global shape and mass distribution of the molecule (13).…”
mentioning
confidence: 99%
“…[9][10][11] The dynamics is observed directly in multiple structures of the same, or similar proteins, as revealed by principal component analysis (PCA), 12 which shows close agreement with the elastic network models (ENMs). 8,[13][14][15][16][17][18][19][20][21] The ENMs have proven their ability to sample efficiently conformational space. Especially noteworthy has been their ability to agree with the conformational transition direction between two forms of the same protein.…”
Section: Introductionmentioning
confidence: 99%